Diskursus Integrasi Islam dan Sains: (Peluang dan Tantangan Sains dalam Islam Perspektif Nidhal Guessoum serta Implikasinya Bagi PTKI/PTKIN) - Abdul Mujib (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This article addresses the theme of integration between Islam and science, focusing on the perspective of Nidhal Guessoum and its implications for Islamic Higher Education Institutions (PTKI) and State Islamic Universities (PTKIN). Through literature review, this discourse explores various opportunities and challenges related to the efforts to combine scientific principles with religious values in the context of Islam. The discussion highlights the thoughts of Nidhal Guessoum as one of the figures advocating for a balanced integration between Islam and science. Additionally, this abstract also examines its impacts on the curriculum and teaching approaches in PTKI/PTKIN. This research presents deep insights into how the integration between Islam and science can be effectively implemented in religious-based higher education environments.